Factors influencing Key Audit Matters Disclosure in Audit Reports of Companies Listed on Market Alternative for Investment (MAI) - Wichianrak, Jittima; Rattanamanee, Jirawan; Churat, Charinrat; laosakun, Techin; Tripipat, Thammachat; Sumritpradit, Panya; Sakulpradit, Pitchaya; Suttipun , Muttanachai; Sattayarak , On-anong (Business Administration and Management Journal Review, 2021)
This research aims to examine the level of key audit matters (KAM) in the audit reports of companies listed in MAI during 2016-2018 and factors influencing key audit matters disclosure. The population and sample size of this study is 114 companies. Descriptive statistics, infer statistics and multiple regression have been analysed. The results show that there is an increasing trend of KAM disclosures, the average of KAM topic disclosure is 1.73 topics, and the average of KAM words disclosure is 643.89 words. Furthermore, researcher found there is a significant negative relationship between return on Asset and the KAM disclosures, whereas changing auditor during the study period, resource industry sector, and technology industry sector factors has a significant positive relationship with the KAM disclosures.